Evaluasi Tingkat Keberhasilan Kegiatan Reklamasi Tambang Batubara PT XX - Hafiz Saputra; Ibrahim Ibrahim; Yohanes Budi Sulistioadi; Harjuni Hasan (Universitas Mulawarman, 2026)
Coal mining activities have the potential to alter landscapes, reduce soil quality, and disrupt ecosystem functions. Reclamation is a mandatory effort to restore environmental functions and improve the productivity of post-mining land. This study aimed to evaluate the success level of coal mine reclamation activities at PT Ghani Raya Mandiri and assess the physical and chemical properties of soil as a revegetation growth medium. A quantitative descriptive survey approach was employed through field observations, laboratory analyses, and evaluation of company reclamation documents. The assessed parameters included backfilling, land recontouring, topsoil spreading, revegetation, acid mine drainage management, and vegetation maintenance. The results indicated that the overall reclamation success rate reached 65.49%, which falls into the moderate category. Backfilling achieved 70.36%, land recontouring 48.49%, topsoil spreading 21.87%, and revegetation recorded a plant survival rate of 80.06%. The average soil pH was 5.53, indicating suitable conditions for plant growth, while treated water quality showed an average pH of 6.79, complying with environmental quality standards. Soil conditions in reclaimed areas generally exhibited low fertility, characterized by low organic carbon content, available phosphorus, and cation exchange capacity. The study demonstrates that reclamation activities have produced satisfactory results; however, improvements in land shaping, topsoil management, and revegetation implementation are still required to enhance long-term reclamation success and ecosystem recovery.